HUBUNGAN KEAKTIFAN IBU DALAM KEGIATAN POSYANDU DENGAN PERTUMBUHAN DAN PERKEMBANGAN BALITA - sumirat, widhi (Akademi Keperawatan Pamenang, 2012)
IHC is a form of community participation in health sector which is managed by a cadre with the object of the whole community Liveliness of families, especially mothers would have an effect on child health status of children under five. In societies still got an active mother to the neighborhood health center and who is not active, the mother of an active and inactive obtained status and growth and development of children under five are normal and there is also abnormal.The research design used in this study is correlational with the case control approach. The population was all mothers in posyandu, the sample was mothers who came to the neighborhood health center during the study and inclusion criteria with a total 22 peopleThe data analysis was done by connecting the activeness of the mother in a neighborhood health center activities with growth and development of young children, analyzed in a descriptive analysis. Results showed that mothers who are active to posyandu 18 respondents (81.8%) while the inactive have four respondents (18.2%). Status of growth and development of normal infants of mothers who were active 36.3% and that is not normal is 45.5%. While the status of normal growth and development of infants of mothers are not active are 27.2% and that is not normal is 54.6%. From the results showed no relationship between activeness of mothers with infant growth and development.